2021
DOI: 10.1017/cjn.2021.102
|View full text |Cite
|
Sign up to set email alerts
|

Guillain Barre Syndrome as a Complication of COVID-19: A Systematic Review

Abstract: Background: In January 2020, the first case of Guillain Barre syndrome (GBS) due to COVID-19 was documented in China. GBS is known to be postinfectious following several types of infections. Although causality can only be proven through large epidemiological studies, we intended to study this association by a thorough review of the literature. Methods: We searched PubMed, EMBASE, and Google scholar and included all papers with English or Spanish full text and original data of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
103
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 108 publications
9
103
2
1
Order By: Relevance
“…A worse course of GBS was observed in older patients who had a more severe course of COVID-19 infection. In the described case, the risk factor for GBS was only the patient's sex (GBS is more prevalent in men) [4,19]. Moreover, the relatively young age of the patient, the mild course of COVID-19, and the prompt treatment could positively affect the course of GBS.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A worse course of GBS was observed in older patients who had a more severe course of COVID-19 infection. In the described case, the risk factor for GBS was only the patient's sex (GBS is more prevalent in men) [4,19]. Moreover, the relatively young age of the patient, the mild course of COVID-19, and the prompt treatment could positively affect the course of GBS.…”
Section: Discussionmentioning
confidence: 84%
“…A total of 72.1% (49/68) of patients with post-COVID-19 GBS achieved a partial or complete remission, whereas 5% (4/68) died [18]. In the study by Aladawi et al, which reviewed 109 cases of post-COVID-19 GBS, 40/99 patients required intensive care treatment, 33.3% (33/99) required mechanical ventilation, and 6.1% (6/99) of patients died [19]. A worse course of GBS was observed in older patients who had a more severe course of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 review identified a total of 109 published cases of GBS with confirmed SARS-CoV-2 infection. Although causality could not be proven, the authors found that AIDP with facial palsy was the most common presentation [ 27 ]. On the other hand, an epidemiological and cohort study by Keddie and colleagues did not find evidence of a causative relationship between SARS-CoV-2 and GBS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies evaluating GBS cases which has developed after COVID-19, it has been reported that the AIDP form of GBS is seen most frequently, followed by AMSAN and AMAN forms, respectively (15,16). While our study was conducted on all forms of GBS, the fact that this study was conducted only on the AIDP form of GBS and not including AMAN and AMSAN forms in the study may have caused different results for CMAP and SNAP amplitude values of nerves between two studies.…”
Section: Discussionmentioning
confidence: 99%